Analisis Kekuatan Massa Batugamping Dengan Menggunakan Kaidah Hoek-Brown Failure Criterion-Roclab di Daerah Gunung Sudo Kabupaten Gunung Kidul Yogyakarta - R. Andy Erwin Wijaya; Dianto Isnawan (PROMINE, 2015)
The research area is a limestone quarry region prospect, located in Gunung Sudo, Gunung KidulRegency, Special Region of Yogyakarta Province. Safety factor of bench in limestone quarry isextremely determined by rock mass quality. The aim of this research is analyzing of rock massstrength of limestone in the quarry prospect using the Hoek-Brown failure criterion. The researchused quantitative method. To obtain rock mass strength analysis of limestone needs someparameters. The main parameters are uniaxial compressive strength of intact rock, GSI, lithology,disturbance factor, unit weight and application for slope (height). To solve this analysis is assisted byRoclab software. The Roclab is a software program for determining rock mass strength parametersbased on the generalized Hoek-Brown failure criterion. Final result of the research will be used forsafely mine design of the limestone quarry.